Corrosion behavior, antibacterial ability, and osteogenic activity of Zn-incorporated Ni-Ti-O nanopore layers on NiTi alloy. (20th January 2022) - Sun, Yonghua; Zhao, Yuyu; Zhang, He; Rong, Youjie; Yao, Runhua; Zhang, Yi; Yao, Xiaohong; Hang, Ruiqiang
Highlights: Zn-incorporated nanopores layers with different lengths were prepared on the NiTi substrate through anodization and hydrothermal treatment. The loaded amounts and release kinetics of Zn ions was controlled by the Ni-Ti-O nanopores. Zn incorporation enhanced the corrosion resistance. Zn-incorporated nanopores layers enhanced the antibacterial property and exhibited long-lasting antibacterial ability. Zn incorporation promoted the generation of alkaline phosphatase products and significantly promotesd type I collagen synthesis and extracellular matrix mineralization. Abstract: Development of bone fixation devices with excellent corrosion resistance, antibacterial ability, and osteogenic activity is critical for promoting fracture healing. In this study, Zn-incorporated nanopore (NP) layers were prepared on the NiTi alloy through anodization and hydrothermal treatment. Results show that Zn can be evenly incorporated into the NP layers in the form of ZnTiO3 . The Zn-incorporated samples exhibit good corrosion resistance and significantly reduce Ni 2+ release. Meanwhile, the samples can continuously release Zn 2+, which is responsible for excellent long-term antibacterial ability. Furthermore, the synergetic effect of Zn 2+ release and nanoporous structure of the NP layers endues the NiTi alloy excellent osteogenic activity, as verified by upregulated alkaline phosphatase activity, secretion of type I collagen, and extracellular matrix mineralization. Therefore, Zn-incorporated Ni-Ti-O NP layers have great potential as biomedical coatings of NiTi-based implant materials. Graphical abstract: Image, graphical abstract